QUALITY OF SPENDING AND HUMAN DEVELOPMENT: DOES ACCOUNTABILITY MATTER? - Yusuf Dwiantoro; Khoirunurrofik (Juremi: Jurnal Riset Ekonomi, 2025)
Based on an equivalent level of expenditure, some districts achieve a high Human Development Index (HDI) while others lag behind. This indicates that other factors influence the achievement of a high HDI. This paper examines the link between public spending, governance, and human development. The role of governance is measured by the level of accountability. Empirical studies are conducted using district-level panel data in Indonesia. The results in this paper suggest that public expenditure alone is insufficient for achieving a good human development outcome. However, when governance is involved, public expenditure in the health sector becomes effective in increasing HDI in districts with high local government accountability, and vice versa is not effective in districts with low accountability. Therefore, local government accountability needs to be strengthened to improve the quality of human development.